GlycoForm and Glycologue: two software applications for the rapid construction and display of N-glycans from mammalian sources. - DAVEY, GAVIN; MCDONALD, ANDREW; TIPTON, KEITH (My University, 2010)
Background: The display of N-glycan carbohydrate structures is an essential part of glycoinformatics. Several tools exist for building such structures graphically, by selecting from a palette of symbols or sugar names, or else by specifying a structure in one of the chemical naming schemes currently available. Findings: In the present work we present two tools for displaying N-glycans found in the mammalian CHO (Chinese hamster ovary) cell line, both of which take as input a 9-digit identifier that uniquely defines each structure. The first of these, GlycoForm, is designed to display a single structure automatically from an identifier entered by the user. The display is updated in real time, using symbols for the sugar residues, or in text-only form. Structures can be added to a library, which is recorded in a preference file and loaded automatically at start. Individual structures can be saved in a variety of bitmap image formats. The second program, Glycologue, reads a file containing columnar data of nine-digit codes, which can be displayed on-screen and printed at high resolution. Conclusion: A key advantage of both programs is the speed and facility with which carbohydrate structures can be drawn. It is anticipated that these programs will be useful to glycobiologists, systems biologists and biotechnologists interested in N-glycosylation systems in mammalian cells.
PUBLISHED
Keywords: Biochemistry; glycoinformatics; N-glycans; Smart & Sustainable Planet